Extracapsular Mandibular Condyle Fractures Are Associated with Severe Blunt Internal Carotid Artery Injury: Analysis of 605 Patients. Issue 4 (October 2015) - Vranis, Neil M.; Mundinger, Gerhard S.; Bellamy, Justin L.; Schultz, Benjamin D.; Banda, Abhishake; Yang, Robin; Dorafshar, Amir H.; Christy, Michael R.; Rodriguez, Eduardo D.
Abstract : Background: Mandibular condyle fractures are common following facial trauma and carry an increased risk for concomitant blunt carotid artery injuries. Further elucidation of this relationship may improve vascular injury screening and management. Methods: A retrospective cohort study was performed for all patients sustaining condylar fractures presenting to a large trauma center over twelve years. Fracture locations were classified according to the Strasbourg Osteosynthesis Research Group (1, condylar head; 2, condylar neck; and 3, extracapsular condylar base). Carotid artery injury severity was based on the Biffl scale. Severe vascular injury was defined as a Biffl score greater than I. Results: 605 patients were identified with mandibular condyle fractures consisting of 21.0 percent ( n = 127) condylar head; 26.8 percent ( n = 162) condylar neck; and 52.2 percent ( n = 316) extracapsular condylar base. The incidence of vascular injuries in this population was 5.5 percent ( n = 33), of which 75.8 percent ( n = 25) were severe. Severe vascular injuries occurred in 1.6 percent ( n = 2) of condylar head, 2.5 percent ( n = 4) of condylar neck, and 6.0 percent ( n = 19) of extracapsular condylar base fractures ( p < 0.05). Extracapsular condylar base fractures were independently associated with a 2.94-fold increased risk of a severe blunt carotid artery injury compared with other condyle fractures on multivariable analysis ( p < 0.05). Conclusions: Extracapsular subcondylar fractures should heighten suspicion for concomitant blunt carotid artery injury. The data support a force transmission mechanism of injury in addition to direct injury from bony fragments. CLINICAL QUESTIONS/LEVEL OF EVIDENCE: Risk, II.